Analysis of Android-Based Fitness Testing and Measurement Application - Ricky, Ricky; Rahmat, Ade; Hardika, Nevi (Joska: Jurnal Isori Kampar, 2025)
Objectives: This study aims to analyze the performance outcomes of 20-meter sprint and shuttle run tests among students participating in athletic extracurricular activities at SMPN 1 Teluk Batang, West Kalimantan, Indonesia. The study evaluates the effectiveness of an Android-based fitness testing and measurement application in assessing speed and agility as foundational physical competencies for athletics, with particular relevance to the standardized athlete monitoring framework of the All Indonesia Athletics Association (PASI). Methods: A descriptive quantitative research design was employed, involving ten purposively selected students (aged 12–14 years) who had undergone structured athletic extracurricular training for a minimum of six consecutive months. The 20-meter sprint test was administered to measure maximum running speed, while the shuttle run test was used to quantify agility. Data were analyzed using descriptive statistics including mean, standard deviation, and percentage of achievement relative to established ideal benchmark values. Performance classification followed a four-tier categorical framework (Excellent, Good, Average, Poor). Ethical clearance was obtained prior to data collection. Results: In the 20-meter sprint test, one participant (10%) achieved the Excellent category, six (60%) were classified as Good, and three (30%) fell within the Average category. In the shuttle run test, seven participants (70%) achieved the Good category, while the remaining three (30%) were classified as Average. No participant was classified as Poor in either assessment. Collectively, 70% of participants demonstrated performance at or above the Good threshold across both physical fitness domains. Conclusion: Participation in structured athletic extracurricular programs is positively associated with measurable improvements in speed and agility among early-adolescent students. Android-based fitness testing tools demonstrate promising utility in standardizing field-based assessments within the PASI coaching ecosystem. Future research involving larger, more diverse samples and longitudinal designs is recommended.